2021
DOI: 10.1186/s40798-021-00334-6
|View full text |Cite
|
Sign up to set email alerts
|

Female (Under) Representation in Exercise Thermoregulation Research

Abstract: Background Despite an increasing rate of women participating in professional sports, emergency services, and military settings where they are exposed to exertional heat stress, our understanding of female thermoregulation and the detrimental effects of heat on women’s performance, especially regarding the menstrual cycle, is limited. This review aimed to quantify the representation of women in exercise thermoregulation research between 2010 and 2019 and the frequency that these articles reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
34
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 50 publications
(74 reference statements)
3
34
1
Order By: Relevance
“…Whereas others have audited numerous topics within a defined set of SSSM journals over a specified period [ 2 , 3 , 4 ], we examined all published literature (~50 years) on a narrow range of topics across all available SSSM journals. Indeed, our findings are similar to the 21% representation identified in an audit of a specific SSSM topic across all journals [ 5 ]. The low total involvement of female participants in the present audit reflects both the lower number of studies involving female-only cohorts, as well as lower numbers of women within the sample among the 14–33% of studies with mixed-sex cohorts.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Whereas others have audited numerous topics within a defined set of SSSM journals over a specified period [ 2 , 3 , 4 ], we examined all published literature (~50 years) on a narrow range of topics across all available SSSM journals. Indeed, our findings are similar to the 21% representation identified in an audit of a specific SSSM topic across all journals [ 5 ]. The low total involvement of female participants in the present audit reflects both the lower number of studies involving female-only cohorts, as well as lower numbers of women within the sample among the 14–33% of studies with mixed-sex cohorts.…”
Section: Discussionsupporting
confidence: 86%
“…Investigations on exclusively female cohorts accounted for 0–8% of studies across different performance supplements, similar to the 4–13% previously reported across a range of exercise/sports themes [ 2 , 3 , 4 , 5 , 6 ]. There is no evidence that the attention drawn to this inequity in research participation [ 3 ] has yet translated to changes in practice, since the proportion of female-only studies published over the previous 5 and 10 years (0–7% and 0–8%, respectively) is similar to the overall time period.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The urgency of the need to address the sex disparity across SSSM research is receiving substantial publicity within scientific literature (Elliott-Sale et al, 2021;Hutchins et al, 2021;Martínez-Rosales et al, 2021) and popular/social media (Yu, 2018(Yu, , 2021. It is therefore important to efficiently direct the current enthusiasm for research on the female athlete into high-quality and meaningful outputs.…”
mentioning
confidence: 99%
“…Conducting such audits across SSSM topics may produce information to help direct future research activities in a systematic and expedient manner. Examples of such audits are beginning to appear (Brookshire, 2016;Costello et al, 2014;Cowley et al, 2021;Hutchins et al, 2021). However, implementing a more standardized audit protocol will optimize the outputs and interpretation of such audits, ensuring that comparisons can be made across time and across SSSM topics.…”
mentioning
confidence: 99%